Management of yam diseases: IITA research guide, No. 39 - Hahn, S. (1992)
Different species of yams are grown in the "yam zone" of West Africa. In field and storage, yams are exposed to various diseases caused by viruses, bacteria, fungi, and nematodes. Yam diseases can be controlled by several integrated control practices.